UI/UX Redesign of the ‘GOBIS’ Public Transportation Application in Surabaya using the Design Thinking Method - Barmin, Aidah Maryam; Wati, Seftin Fitri Ana; Mukhlis, Iqbal Ramadhani (Institut Teknologi Dirgantara Adisutjipto, 2025)
GOBIS is one of the public transportation applications launched by the Surabaya City Government in 2018. However, in the use of GOBIS there are still various problems, A pre-evaluation using the System Usability Scale (SUS) with 20 respondents yielded a score of 45.15—well below the average of 68 and classified as ‘very poor. This study uses the design thinking method with 5 stages, namely empathize, define, ideate, prototype, and testing. Testing on the prototype results involved 5 respondents using the System Usability Scale (SUS) method and maze.co tools to get task results automatically. As a result, this new UI/UX design has gone through usability testing using maze and produced a score of 93/100 and an increase in the SUS score from 45.152 to 82, which is a good category. These results demonstrate that the redesigned interface better aligns with user needs and is more user-friendly, achieving a 36.85-point increase in SUS.